Mail notification system using SMS - Intan Azira, Azahar (2011)
Mail Management System Using SMS (MANSUS) is a system that helps Residence Office process student mail more efficiently.The system is so called efficient because as we all know there are thousands of students live in university.All the mails that posted to them will be sent to Residence Office to be arranged and organized according to their name or room number.So,to be more systematic in managing all the mails,I build the system so called MANSUS so that the staffs no need to serve every student when they come to the office and asked for their mail. MANSUS is a stand-alone system whereby the system has to be installed in the computer before using the system. To be more ease for staff instead of they need enter all the students' name,they just have to connect the text scanner to the PC and read the name on the mail thus the data will be added in the database.The system will then automatically retrieve student's name in the database based on the name that scanned.After the confirmation is made, the notification will be sent to students via mobile phone. Once the student receives the notification, they can pick up their mail at Residential Office.As a conclusion,this system is made for staffjust to make ease to control the flow of students' mail as well as students being notify about their mail.